Oracle developer/2000 handbook - Stowe, Michael W. (Prentice Hall PTR, 1999)
Oracle no longer ships hard-copy documentation with Developer/2000. For database professionals, this systematic, real-world guide is the best replacement available. Don't just learn what can be done with Oracle Developer/2000: learn what should be done, and the best ways to accomplish it. Walk step by step through the entire Developer/2000 toolset, including forms, reports, graphics, data modeling and design tools, and much more. Oracle Developer/2000 Handbook includes coverage of critical topics often neglected in discussions of Oracle Developer/2000, including SQL tuning and GUI standards.